2022
DOI: 10.14791/btrt.2022.0030
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Meningioma: Clinical Characteristics, Prognostic Factors and Survival Outcome

Abstract: Background Anaplastic meningioma is very rare and is generally known to have a poor prognosis. However, due to its rarity, the relationship between clinical prognosis and prognostic factors is not clear. We analyzed the prognostic factors influencing survival outcomes of patients with anaplastic meningioma. Moreover, we analyzed on the progression pattern and the response to treatment about anaplastic meningioma. Methods Retrospective review of 48 patients with diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…3 Meningiomas harboring homozygous deletions of CDKN2A/B are characterized by high recurrence rates independent of WHO grade, DNA methylation class, sex, age, and tumor location. 4 Additionally, heterozygous loss, mutations, and promoter methylation of CDKN2A were strongly associated with recurrent meningiomas and a high Ki-67 index. 8 Physiologically, the proteins encoded by CDKN2A/B halt the cell cycle; consequently, homozygous loss leads to dysregulated cell cycle progression and uncontrolled proliferation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…3 Meningiomas harboring homozygous deletions of CDKN2A/B are characterized by high recurrence rates independent of WHO grade, DNA methylation class, sex, age, and tumor location. 4 Additionally, heterozygous loss, mutations, and promoter methylation of CDKN2A were strongly associated with recurrent meningiomas and a high Ki-67 index. 8 Physiologically, the proteins encoded by CDKN2A/B halt the cell cycle; consequently, homozygous loss leads to dysregulated cell cycle progression and uncontrolled proliferation.…”
Section: Discussionmentioning
confidence: 96%
“…2 The histopathological hallmark of anaplastic meningioma is high mitotic activity, cellular atypia, and frequent necrosis, with 2021 WHO incorporating genomics and molecular data into this classi cation. 3,4 These aggressive features underscore the urgent need for effective management strategies, especially in recurrent diseases, where treatment guidelines are notably scarce. Literature on the toxicity associated with re-irradiation in this speci c clinical setting is conspicuously limited, accentuating the necessity for a comprehensive evaluation of outcomes related to local control, overall survival, and treatment-related adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…An isolated case of anaplastic meningioma was also present. A fact sometimes overlooked and under-investigated is that these rare meningiomas can metastasize to extracranial locations, reported in up to 16.6% of cases in a recent retrospective review by Seo et al 39 and carry an overall poor prognosis. These tumours may exhibit suspicious features; however, some studies showed no significant differences in appearance of benign and anaplastic subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Age and clinical status are well-established prognosticators [ 24 ]. As concerns the extent of resection, while GTR is a common goal in lower grade meningioma, its role in grade III meningioma management is still not clear [ 25 , 26 ]. In progressive meningioma, GTR can be very difficult to achieve due to previous treatments.…”
Section: Discussionmentioning
confidence: 99%